TRANSFORMING AND EVALUATING EFL SPEAKING SKILLS WITH AUGMENTED REALITY: AN AR-BASED MODULE APPROACH - Fitayanti, Sri (English Review: Journal of English Education, 2024)
This study explores AR technology's role in assessing EFL students' speaking skills, aiming to enhance language learning experiences. Its main objective is to design and validate an AR-based assessment module for evaluating speaking proficiency. Employing a mixed-methods approach, the research investigates AR's impact on student engagement, learning outcomes, and language proficiency. It involves forty-five EFL learners from IAIN Fattahul Muluk Papua, using both quantitative and qualitative methods to collect data, including pre-tests, post-tests, interviews, and observations. The AR-based module integrates technology into authentic assessment scenarios, offering immersive learning experiences. Results show a significant improvement in post-test scores, with the mean score increasing from 2.4 (pre-test) to 3.9 (post-test), indicating the module's efficacy. The paired-samples t-test revealed a significant difference (t (59) = -10.24, p < .001) between pre-test and post-test scores. Qualitative insights highlight increased engagement, positive experiences, and enhanced confidence among students. These findings underscore AR's potential in language education, particularly in speaking assessment. The integration of AR-based modules presents a promising approach for enhancing language teaching and learning, providing immersive experiences. This has implications for educators and practitioners seeking innovative language assessment methods